Rearrangement of 11q23 Chromosome Region in Acute Myeloid Leukemias in Children - EV Fleishman; OI Sokova; AV Popa; GA Tsaur; LN Konstantinova; OM Plekhanova; MV Strigaleva; ES Nokhrina; VS Nemirovchenko; OR Arakaev (Клиническая онкогематология)
Aim. To study characteristics of 11q23 involvement, age-specific differences in the incidence of these chromosomal markers in acute myeloid leukemias (AML) in children, and to determine their prognostic significance in patients treated according to the protocols applied in leading Russian pediatric hematological clinics.